COMPARATIVE ANALYSIS OF STEVEDORING LABOR PERFORMANCE IN THE SEA TOLL PROGRAM: INSIGHTS FROM INDONESIA AND THE PHILIPPINES - Elfrida Ratnawati Gultom; I Gede Yudi Arsawan; Ildar Begishev (Kanun Jurnal Ilmu Hukum, 2025)
This study conducts a comparative analysis of stevedoring labor performance within the Sea Toll program in Indonesia and the Philippines, focusing on efficiency, technology, and worker welfare. It aims to identify the key factors influencing the effectiveness of stevedoring labor in both countries. Employing a normative legal method alongside a comparative study approach, the findings indicate that the performance of stevedoring labor in the Philippines is superior to that in Indonesia, particularly regarding work efficiency, technological implementation, and worker welfare. The Philippines has successfully established a skills certification system through the Technical Education and Skills Development Authority (TESDA), implemented port automation systems such as the Cargo Handling Management System (CHMS) and the Port Community System (PCS), and ensured labor protection in accordance with the Philippine Labor Code and the Occupational Safety and Health Standards (OSHS) Act. In contrast, Indonesia faces significant challenges, including difficulties in implementing skill standards, inadequate port infrastructure, and limited social protection for workers, despite existing regulations such as Law Number 17 of 2008 on Shipping and the Minister of Manpower Decree Number 100 of 2004. Key determinants of stevedoring labor effectiveness include labor regulations, technological availability, training systems, welfare, and work culture. The Philippines has demonstrated greater success in integrating these factors into its operational framework. Therefore, Indonesia could benefit from adopting the Philippines' robust regulatory framework, skills certification system, automation technology, and enhanced worker welfare protections.